New ultra-small design and high performance of an 8×8 massive MIMO antenna for future 6G wireless devices - Karrar Shakir Muttair; Karrar Khaleel Aljawaheri; Mujtaba Zuhair Ali; Oras Ahmed Shareef; Mahmood Farhan Mosleh (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The demand for the array antenna that consists of multiple ports has increased in recent years, because of its main importance in reducing noise and interference between users. In this paper, we propose a new method for designing an 8×8 (16-ports) multi-input and multi-output (MIMO) antenna. This method relied on the Micro Strip mechanism so that we presented a small antenna that operates at wide and multi-bands of millimeter waves (Mm-Waves). According to the information curves generated by the CST experimental software, it was observed that the proposed antenna operates well from 36 to 60 GHz. Therefore, the antenna achieved the best results in terms of many most important parameters, the reflection coefficient is <-10 dB, return loss is <-25 dB, and voltage standing wave ratio (VSWR) is < 2. In addition, the efficiency of the antenna for all frequencies from 70% to 97%, the envelope correlation coefficient (ECC) is <0.001, and the diversity gain (DG) is 10 dB for all frequencies, while the maximum gain achieved by the antenna is 9 dB at 46 GHz. All these good results achieved by the antenna make it the prominent and potential element in most of the future 6G wireless communication systems.